(untitled) (Itinera, 2023)
At the turn of the nineteenth and twentieth centuries, through the eurhythmics of Émile Jaques-Dalcroze, a new relationship between music and movement was established, which closely involved dance and architecture. Our emphasis, here, will be put on the transformations related to space, with regard to the stage reform by Adolphe Appia, Dalcroze’s friend and collaborator. It is through Appia’s drawings, the Rhythmic Spaces, made between 1909 and 1911, that the connection between living movement and architecture will be approached. In particular, one calls in question the status of straight lines, horizontal and vertical, of which the staircases, on the drawings, are emblematic. These lines, contrasting with the curving and serpentines lines that mark the influence of the dancing movement in the paintings from that period, must be understood with respect to the Dalcrozian conception of rhythmic feeling. Aliveness, for him, which is not to be separated from the relationship to measure - itself alive -, can be acquired by varied and complex exercises of marching within the framework of rhythmic education. Through architecture arises a musical conception of space in rupture with the perspectival conception of pictural space, as the former doesn’t dissociate any more mobility and immobility, aliveness and inertia, grace and gravity.